Pressure reveals unique conformational features in prion protein fibril diversity - Torrent, J; Martin, D; Noinville, S; Yin, Y; Doumic, M; Moudjou, M; Béringue, V; Rezaei, H (Springer Nature, 2019)
The prion protein (PrP) misfolds and assembles into a wide spectrum of self-propagating quaternary structures, designated PrPSc. These various PrP superstructures can be functionally different, conferring clinically distinctive symptomatology, neuropathology and infectious character to the associated prion diseases. However, a satisfying molecular basis of PrP structural diversity is lacking in the literature. To provide mechanistic insights into the etiology of PrP polymorphism, we have engineered a set of 6 variants of the human protein and obtained PrP amyloid fibrils. We show that pressure induces dissociation of the fibrils, albeit with different kinetics. In addition, by focusing on the generic properties of amyloid fibrils, such as the thioflavin T binding capacities and the PK-resistance, we reveal an unprecedented structure-barostability phenomenological relationship. We propose that the structural diversity of PrP fibrils encompass a multiplicity of packing defects (water-excluded cavities) in their hydrophobic cores, and that the resultant sensitivity to pressure should be considered as a general molecular criterion to accurately define fibril morphotypes. We anticipate that our insights into sequence-dependent fibrillation and conformational stability will shed light on the highly-nuanced prion strain phenomenon and open the opportunity to explain different PrP conformations in terms of volumetric physics.